Surviving field research [ working in violent and difficult situations - Sriram, Chandra Lekha , 1971- (Routledge, 2009)
This text guides researchers in conducting research in situations of violent conflict or human rights abuses. It informs the reader of the ongoing debates about responsible scholarship and explains how to identify and address challenges in conducting qualitative research in difficult circumstances.